Analysis of the Role of Stakeholders in Policy Handling Radicalism in Poso District - Galip Lahada; Yunruth H. Marande; Roma Tressa (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
This research aims to analyze the roles and relationships between stakeholders in policies to prevent radicalism in Poso district. The actors involved in the counter-radicalism policy in Poso Regency consist of state actors such as BNPT RI, Poso Regent, Poso Kesbangpol, Poso Ministry of Religion, Kodim 1307/ Poso, Poso Police/Densus 88, as well as non-state actors consisting of the Poso FKUB, academic and former terrorist convict. The results of the research show that the counter-radicalization policy in Poso Regency is top-down in nature where state actors have a very strong influence in counter-radicalization decision making in Poso Regency, this is proven by the issuance of Poso Regent's Decree Number 188.45/0474/2021 concerning the Formation of an Integrated Handling Team Poso District Level Social Conflict in 2021 to implement the Poso District Integrated Action Plan for Handling Social Conflict in the Region in 2020-2022, where all policy formulators are government actors in Poso.